Influencing factors that support and build aged care research capacity: Staff perspectives. Issue 1 (February 2020) - Watson, Karen; Hatcher, Deborah; Good, Anthony
Abstract: Background: Strategic collaborative networks between care staff and researchers can be a powerful means of improving the provision of safe and quality care. Aged care staff hold vital information on research practicality and ease of implementation in the clinical setting. Aged care staff are best positioned to advise on a study's feasibility in the clinical environment and for the particular residents in their care, regardless of the fact that they are often not involved in the research process. Aim: To explore aged care staff attitudes towards research particularly the influencing factors that promote and sustain care staff participation in research in the residential aged care facility (RACF) setting. Methods: Qualitative semi-structured interviews were conducted at two aged care facility sites in Sydney with 10 aged care staff before and after their participation in a randomised controlled trial on their ward. The interviews explored aged care staff perceptions of the importance of research, staff compliance and factors that influence research conducted in the RACF setting. Findings: Aged care staff reported on the importance of conducting research in RACFs. The barriers to staff participation included insufficient time (50%), lack of belief in intervention effect (30%), deficits in research knowledge (40%) or support (30%). Research perceived as practical (40%) that could be conducted unobtrusively (60%), provided tailored education (70%) with effective communication (50%) between researcher and aged care staff, was more favourable for staff participation. Discussion: Aged care staff recognised that findings from research when implemented was important for improving quality care provision but it was challenging to conduct research in the RACF setting. Implementing strategies that support aged care staff research time away from clinical tasks, access to research education and foster communication between academic and staff can improve care staff participation in research. Conclusion: Focused strategies fostered by collaborative partnerships between aged care staff, academic researcher and industry management can promote and sustain the research capacity of staff caring for older people in RACFs.